2020
DOI: 10.1103/physrevfluids.5.064602
|View full text |Cite
|
Sign up to set email alerts
|

Transition from non-swirling to swirling axisymmetric turbulence

Abstract: Strictly axisymmetric turbulence, i.e., turbulence governed by the Navier-Stokes equations modified such that the flow is invariant in the azimuthal direction, is a system intermediate between two-and three-dimensional turbulence. We investigate statistically steady states of this system by direct numerical simulation using a forcing protocol, which allows the injected energy in the toroidal and in the poloidal directions to be tuned independently. A sharp transition between a two-dimensional two-component (2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The theoretical predictions of this system were shown to be in qualitative agreement with experimental measurements of a stirred turbulent wouter.bos@ec-lyon.fr flow in a cylinder, which is only axisymmetric on average [18,19]. This success inspired further theoretical studies of the axisymmetric Euler system [20][21][22][23], and recently the first numerical simulations of strictly axisymmetric turbulence [24][25][26].…”
Section: Non-integer Dimensionssupporting
confidence: 58%
See 3 more Smart Citations
“…The theoretical predictions of this system were shown to be in qualitative agreement with experimental measurements of a stirred turbulent wouter.bos@ec-lyon.fr flow in a cylinder, which is only axisymmetric on average [18,19]. This success inspired further theoretical studies of the axisymmetric Euler system [20][21][22][23], and recently the first numerical simulations of strictly axisymmetric turbulence [24][25][26].…”
Section: Non-integer Dimensionssupporting
confidence: 58%
“…The most recent of these investigations [26] , in which a linear forcing protocol is used, showed that two very different types of flows can be observed in the axisymmetric system, depending on the forcing anisotropy. When only the poloidal components of the flow are forced, a purely poloidal flow is observed with features typical of twodimensional two-component (2D-2C) turbulence, such as an inverse energy cascade and coherent structures.…”
Section: Non-integer Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…2010; Qu, Bos & Naso 2017; Qin et al. 2020), or thin-layer turbulence (Celani, Musacchio & Vincenzi 2010; Benavides & Alexakis 2017; Favier, Guervilly & Knobloch 2019).…”
Section: Introductionmentioning
confidence: 99%